PENILAIAN PELAKSANAAN PROGRAM PENGEMBANGAN AGRIBISNIS PETERNAKAN SAPI POTONG DI KABUPATEN SEKADAU, KALIMANTAN BARAT - Mikael Heri Setiyo Wibowo; Budi Guntoro; Endang Sulastri (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
bjectives of this research were to analyze the characteristic of social demography of farmer’s participated in program and to carryout assessment. The implementation of agribusiness development program of beef cattle farmingin Sekadau Regency. This research was conducted from August until October 2009. One hundred and eight farmers participated in the program as respondents, selected by proportionate random sampling method, from five villages,locations of the program of livestock grant. Data of increasing population, number of investor, social demography characteristic of respondents and income contribution from beef cattle farming were analyzed by quantitative descriptive. Data of program implementation process, input and program implementation were analyzed by qualitative descriptive. Result showed that the beef cattle population increased about 152 heads and the investor increased about58 investors, respondent characteristics were age was 42.30±5.87 years old, majority of education level was on elementary school 43.52%, length of farming experience was 1.61±1,20 years, averages of cattle owning 1.88±1.05Livestock Unit (LU), the number of family support 3.36±1.15 head, and averages of time allocation of farming 0.078±0.082 HOK/LU/day, average income contribution from beef cattle farming was rangery from 8.21-24.09%.Program’s socialization in Sekadau Regency was not effective because many of the farmers had not fully understood about the objective and the implementation of the program, there was a distortion on the selection of farmers whoreceived livestock grant, farmer groups were not established based on the rule, were not involved members the arrangement of group business plan, breed determination and cattle specification, cattle’s specifications were not suitable with the condition. On the implementation step, there was a distortion of the fund, cattle specification and cost burden to the member, difference on mechanism of livestock grant revolving in each village. The increase of beefcattle population had not reached the determined target. It could be concluded that the implementation of agribusiness development program in Sekadau Regency has not been optimal.(Keywords: Social demography characteristic, Program implementation, Beef cattle)